Caracterização da expressão molecular da podoplanina e do Ki-67 nas displasias epiteliais e carcinomas de células escamosas orais : análise da transformação maligna - Ribeiro, Fabiano de Azevedo (2015)
Introduction: Oral squamous cell carcinoma (OSCC) is the most common malignancy in the oral cavity and its development involves a series of molecular mechanisms and may be preceded by oral potentially malignant disorders (OPMDs). Biomarkers expressed on the cell proliferation phase and involved in the invasiveness may lead to a better understanding of the carcinogenesis process. Objectives: To characterize the Ki-67 expression and D2-40 in OPDM and OSCC and their clinically healthy margins and confront the histopathological degrees and clinicopathological data from these lesions. Methods: In this cross-sectional study, we evaluated 25 OPDM, 10 OSCC and their perilesional tissues from May-2013 to July-2014 in the Oral Diagnosis Center. The morphometric alterations were evaluated in OPDM and OSCC by hematoxylin-eosin method and the expression of Ki-67 and podoplanin, qualitatively and quantitatively, by immunohistochemistry. Results: For the group of OPDM, most lesions showed no dysplastic changes on its margins, already in OSCC, 50% had severe OED and 20% moderate and 30% mild OED. In immunohistochemical analysis, compared the lesions and their perilesional tissues, Ki-67 showed a difference in OPDM (p = 0.016) between lesions OPDM and OSCC(p=0.006) and between perilesional tissue and peritumoral tissue (p=0.001). There was a direct relationship between higher degree of OED and greater expression of Ki-67 in OPDM (p=0.010) and its peritumoral tissues (p=0.022). The podoplanin showed higher expression rate in the lesions themselves than in their perilesional and peritumoral tissues, although not significantly different. There was a direct relationship (p=0.001) between severity of OED and expression of podoplanin in OPDM lesions and positive correlation between expression of Ki-67 and podoplanin in OSCC lesions(p=0.000). Conclusions: It was found a gradual increase in ascending order of the expression of molecular markers studied in perilesional tissue, OPDM, peritumoral tissues and OSCC. Besides the significant correlation between cell proliferation and the degree of oral epithelial dysplasia, and the degree of differentiation of OSCC, suggesting Ki-67 as an additional criterion for determine the severity of OPDM. The positive correlation between Ki-67 and D2-40 in OSCC points them as prognostic biomarkers and therapies targeted against cancer. Further studies may reveal a better participation of podoplanin in carcinogenesis.